2013
DOI: 10.1007/s10339-013-0561-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced mental rotation ability in time-space synesthesia

Abstract: Time-space synesthesia is a variant of sequence-space synesthesia and involves the involuntary association of months of the year with 2D and 3D spatial forms, such as arcs, circles, and ellipses. Previous studies have revealed conflicting results regarding the association between time-space synesthesia and enhanced spatial processing ability. Here, we tested 15 time-space synesthetes, and 15 non-synesthetic controls matched for age, education, and gender on standard tests of mental rotation ability, spatial wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 31 publications
4
36
0
Order By: Relevance
“…A similar effect has previously also been shown in a group of five sequence-space synaesthetes by Simner et al (2009), and in group of 15 sequence-space synaesthetes by Brang et al (2013). Our current study therefore represents the third instantiation of this effect.…”
Section: Individual Differences In Mental Rotationsupporting
confidence: 89%
See 4 more Smart Citations
“…A similar effect has previously also been shown in a group of five sequence-space synaesthetes by Simner et al (2009), and in group of 15 sequence-space synaesthetes by Brang et al (2013). Our current study therefore represents the third instantiation of this effect.…”
Section: Individual Differences In Mental Rotationsupporting
confidence: 89%
“…It is already known that levels of intelligence positively 1 There is no evidence of systemaic diference across previous studies in the presence of 2D/3D forms, and the use of 2D/3D rotaion tasks: Simner et al (2009) and Rizza and Price (2012) both used a 3D object rotaion task whereas Brang et al (2013) used a 2D grapheme rotaion. No informaion regarding spaial dimensionality of forms was reported in either Simner et al (2009) or Rizza and Price (2012), although Brang and colleagues concluded that within their sample of synaesthetes (N=117), there was nearly a 50:50 split between those that experienced their forms as 2D or 3D.…”
Section: Individual Differences In Synaesthetesmentioning
confidence: 86%
See 3 more Smart Citations